THE ROLE OF WOMEN IN THE TRADITIONAL NORTH-CAUCASIAN SOCIETY AND IN THE CIVILIZED SPACE OF EUROPE - Harsiev, Boris Magomet-Gireevic (History, Archeology and Ethnography of the Caucasus, 2019)
Within the framework of social anthropology, we examine the role of women in the local culture of the North Caucasian peoples and European society through comparative analysis. Undoubtedly, men have more power as the keepers of house, hearth and family. However, women often have significant informal authority, especially in the domestic sphere, as well as in the sphere of modern production.With the collapse of the traditional family and family relationships, a nation starts to degrade. The conditions for the existence and development of the Caucasian family were completely different from European family existentialism. While the traditional community is built on mutual assistance and tolerance, the modern European community is based on rationalism.It is noteworthy that the national (traditional) and the world (global) cultures are two separate worlds. In each of them, women play a significant role, determined by the nature.
Keywords: Social anthropology; Traditional culture; Gender relations; Emancipation; Family and family relationships; Liberal morality; World culture.